2019
DOI: 10.1111/jphp.13049
|View full text |Cite
|
Sign up to set email alerts
|

LncRNA TapSAKI promotes inflammation injury in HK-2 cells and urine derived sepsis-induced kidney injury

Abstract: Objective To explore the possible mechanism of lncRNA TapSAKI in urine derived sepsis‐induced kidney injury. Materials and methods In vivo urine‐derived sepsis (US) rat model and in vitro LPS‐induced HK‐2 cells were established, and TapSAKI, miR‐22, PTEN, TLR4 and p‐p65 expressions were detected by qRT‐PCR and western blot. RNA precipitation and RNA pull‐down were performed to confirm the interaction between TapSAKI and miR‐22. Results TapSAKI was up‐regulated, miR‐22 was down‐regulated, PTEN, TLR4 and p‐p65 e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
36
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(37 citation statements)
references
References 26 publications
1
36
0
Order By: Relevance
“…in other words, silencing of Hulc ameliorated the lPS-mediated injury in HMec-1 cells, which was consistent with a previous report (9). Multiple reports have proposed that lncrnas play pivotal roles in sepsis by targeting miRNAs (6,7). For example, NEAT1 upregulated Toll-like receptor 4 to promote sepsis-induced liver injury by sponging let-7a (29).…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…in other words, silencing of Hulc ameliorated the lPS-mediated injury in HMec-1 cells, which was consistent with a previous report (9). Multiple reports have proposed that lncrnas play pivotal roles in sepsis by targeting miRNAs (6,7). For example, NEAT1 upregulated Toll-like receptor 4 to promote sepsis-induced liver injury by sponging let-7a (29).…”
Section: Discussionsupporting
confidence: 90%
“…lncrnas have roles in the regulation of inflammatory responses in sepsis (5). For example, lncrna Transcript Predicting Survival in aKi was demonstrated to facilitate HK-2 cell apoptosis and inflammatory responses in sepsis-induced kidney injury (6). lncRNA hox transcript antisense rna could repress proliferation, and upregulate apoptosis and inflammatory responses in sepsis in vitro (7).…”
Section: Introductionmentioning
confidence: 99%
“…TLR4, an important regulator of the NF-κB signaling pathway, has been shown to regulate cell apoptosis, inflammatory response and oxidative damage of renal tubular epithelial cell in hyperglycemia [42,43]. Notably, a previous study showed that miR-140-5p inhibits pulmonary inflammatory response in ALI by targeting TLR4 [18].…”
Section: Discussionmentioning
confidence: 99%
“…LncRNA can regulate inflammatory response via regulating the related proteins. For example, TapSAKI aggravates inflammatory injury of HK‐2 cells and renal insufficiency induced by urogenic sepsis; upregulation of circulating NEAT1 is closely linked to increased severity and adverse prognosis of sepsis patients . Some studies highlight the significance of CRNDE in diverse diseases.…”
Section: Discussionmentioning
confidence: 99%